Pierre Rosanvallon's political thought : interdisciplinary approaches - Flügel-Martinsen, Oliver; Martinsen, Franziska, 1975-; Sawyer, Stephen W., 1948-; Schulz, Daniel (Bielefeld University Press, 2019)
The work of Pierre Rosanvallon has increasingly found itself at the center of debates in democratic and political theory - although only few of his numerous monographs have thus far been translated from French. This interdisciplinary volume, the first comprehensive collection on his political thought in English, seeks to lay the groundwork for the study of this eminent political thinker and historian. Following a hitherto untranslated opening essay by Rosanvallon, the chapters - written from a variety of disciplinary perspectives including political theory, political science, philosophy, and history - cover a wide range of topics from the history of democracy to sovereignty, populism, and the function of the press in liberal democratic regimes.